2018
DOI: 10.1038/s41467-017-02107-w
|View full text |Cite
|
Sign up to set email alerts
|

Parallel derivation of isogenic human primed and naive induced pluripotent stem cells

Abstract: Induced pluripotent stem cells (iPSCs) have considerably impacted human developmental biology and regenerative medicine, notably because they circumvent the use of cells of embryonic origin and offer the potential to generate patient-specific pluripotent stem cells. However, conventional reprogramming protocols produce developmentally advanced, or primed, human iPSCs (hiPSCs), restricting their use to post-implantation human development modeling. Hence, there is a need for hiPSCs resembling preimplantation nai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
139
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(165 citation statements)
references
References 59 publications
(96 reference statements)
22
139
0
1
Order By: Relevance
“…Recent developments in human embryo culture and new culture conditions for hESCs, will hopefully soon allow us to observe this transition to the XaXi state and investigate the functional roles of XACT and potentially TSIX. [ 98–101 ]…”
Section: Candidate Regulators and Mechanismsmentioning
confidence: 99%
“…Recent developments in human embryo culture and new culture conditions for hESCs, will hopefully soon allow us to observe this transition to the XaXi state and investigate the functional roles of XACT and potentially TSIX. [ 98–101 ]…”
Section: Candidate Regulators and Mechanismsmentioning
confidence: 99%
“…In the second culture formulation, naïve hPSCs are stabilised and propagated in a cocktail of low‐dose 2i, LIF and a PKC inhibitor (t2iL + PKCi) (Table ) . This set of factors can maintain naïve hPSCs that have been generated by NANOG and KLF2– induced , KLF4– induced, or OCT4 , KLF4 , SOX2 and MYC ‐induced reprogramming, by transgene‐free chemical resetting of primed hPSCs and captured directly from preimplantation human blastocysts . Naïve hPSCs maintained in t2iL + PKCi exhibit many of the similarities to 5i/L/A naïve hPSCs including a globally hypomethylated genome (Table ), a close transcriptional alignment with preimplantation human and primate epiblast cells, and, in a proportion of cells, XIST ‐positive active X‐chromosomes (Table ) .…”
Section: Developing Culture Conditions To Sustain Hpscs In a Preimplamentioning
confidence: 99%
“…Many of the drawbacks are also shared with the 5i/L/A cells . Curiously, a subset of naïve hPSC lines grown in RSeT media, a commercial derivative of ‘naive human stem cell medium’, showed transcriptional similarly to t2iL + PKCi cells, whereas other lines in the same RSeT conditions aligned more closely to primed hPSCs …”
Section: Developing Culture Conditions To Sustain Hpscs In a Preimplamentioning
confidence: 99%
“…These similarities are defined in many aspects including dependence on activin A and fibroblast growth factor 2 (FGF2) signaling pathway (Li and Belmonte, 2017), their transcriptional and epigenetic profiles, random X-chromosome inactivation, culture requirements and morphology and their differentiation capacities (Brons et al, 2007;Tesar et al, 2007). Recently, numerous attempts have been made to generate human naïve PSCs by the resetting of primed PSCs (Hanna et al, 2010;Gafni et al, 2013;Takashima et al, 2014), as well as somatic cellular reprograming (Liu et al, 2017;Kilens et al, 2018;Giulitti et al, 2019). It has also been reported that hESCs isolated from preimplantation ICM could be cultured in vitro to acquire a naïve pluripotent state (Guo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%